Genetic divergence in Brassica rapa L. (Bangladesh Journal of Agricultural Research, 2015)
Different multivariate analysis techniques were used to classify 33 Brassica rapa L. genotypes. The genotypes were grouped into five clusters. Cluster I contained the maximum number of genotypes. Cluster III earned the highest cluster mean value for number of primary branches/plant, number of secondary branches/plant, number of siliquae/plant and seed yield/plant. Therefore, more emphasis can be given on cluster III for selecting genotypes as parents for the hybridization program. The highest intra-cluster distance (3.822) was found in cluster I and the lowest (0.000) in cluster V. The highest inter-cluster distance (15.705) was observed between clusters III and V showing wide diversity among the groups. Principal component analysis (PCA) showed that the first three principal components accounted for 99.38 % of the total variation observed. Analysis of the factor loading of the component character indicated that the characters number of siliquae/plant, plant height and days to maturity were found responsible for genetic divergence. The role of number of siliquae/plant in both the vectors was important components for genetic divergence in these materials. Among the possible 528 combinations, the highest inter-genotypic distance (1.5975) was observed between G-27 (BARI sarisha-9 x BARI sarisha-6 S-62) and G-31 (BARI sarisha-15). Considering group and inter-genotypic distance, cluster mean, contribution of different characters towards the total divergence and other agronomic performance the genotypes G- 19 (BARI sarisha-6 x TORI-7 S-48), G-20 (F6 x BARI sarisha-9 S-52), G-27 and G-30 (BARI sarisha-6 x TORI-7 S-37) from cluster III; G-26 (F6 x BARI sarisha-9 S-15) and G-31 from cluster IV and G-33 (BARI sarisha-6) from cluster V would be considered as better parents for future hybridization program.Bangladesh J. Agril. Res. 40(3): 421-433, September 2015